Strategi Pelayanan Tour Leader Biro Haji dan Umroh Untuk Meningkatkan Reapeat Order Calon Jamaah Pada PT. Impressa Media Wisata - Rohimat, Akhman; Sudrajat, Bayu (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2023)
The role of a tour leader is crucial in serving Umrah and Hajj pilgrims, acting as a spiritual guide for them. They must possess in-depth knowledge of the procedures and rules governing the performance of Umrah and Hajj rituals. This research aims to analyze the service strategies of tour leaders at PT. Impressa Media Wisata in an effort to enhance repeat orders from prospective pilgrims in the Hajj and Umrah travel industry. The research methodology employed is a qualitative approach involving interviews and observations of tour leaders, as well as an analysis of relevant documents. The research results highlight indicators of tour leader service quality, including professional attitude, up-to-date information, managerial ability, and time discipline as the main focus. PT. Impressa Media Wisata implements a service strategy that emphasizes the tour leader's patience and friendliness, which is considered a key element in creating a positive experience for prospective pilgrims. The evaluation shows that aligning strategies with positive tour leader characteristics can significantly increase the satisfaction of potential pilgrims and strengthen PT's repeat order potential. Impressa Media Wisata, provides a foundation for increasing effectiveness and attractiveness in the tourism industry.